Water Supply and Regulation of Underground Reservoir in Coal Mine considering Coal-Water Occurrence Relationship - Mingbo Chi; Zhiguo Cao; Quansheng Li; Yong Zhang; Baoyang Wu; Bao Zhang; Yi Yang; Xiaoqing Liu (Geofluids)
Water supply prediction and control is one of the key issues in exploitation of coal mine underground reservoirs (CMUR). In order to investigate the water supply for underground reservoirs in coal mines, the aquifers were classified into three types (types I, II, and III) according to the relative location of aquifers. The discrete element fluid structure coupling numerical simulation model is constructed according to the classification results. The numerical simulation parameters are inversed based on the surface subsidence data and the advance support pressure, and then, the disturbed characteristics and water pressure variation law of different types of aquifers are studied. The research results show that the maximum water inflow of type III, type II, and type I aquifers is 739 m3/h, 377 m3/h, and 279 m3/h, respectively. The dynamic calculation process of underground reservoir capacity under mining disturbance is refined, and the regulation and storage methods of underground reservoir are preliminarily put forward.